MODIFICATION OF LOCATION QUOTIENT (LQ) METHOD IN MAPPING CONDITIONS OF FOOD SECURITY IN WEST JAVA PROVINCE - Roni Kastaman; Moehammad Fauzi; Besthari D. A. Pambudi; Shinta A. Permatasari; Rakha Zahra Raihan (Universitas Padjadjaran, 2023)
West Java Province, according to Indonesia’s statistical data, is a province with a large population and area of food crop production in Indonesia. So that, it becomes a national strategic food barn. The development of food security planning in this province is important and will also have an impact on national food security. In planning, many regional approaches have been used, for example, the commodity-based approach which is used as a reference in zoning-based development planning, or commonly known as the Location Quotient (LQ) approach. The LQ method in this study was slightly modified by changing the main commodity variables with variables from the existing Food Security dimensions based on the original LQ value ≥ 1 with a range of 0 to 0.75 based on the average value of food security measurement standards with the example of West Java. The basic formula for LQ after the modified one can provide an overview of the condition of food security that occurs in urban districts in West Java Province. The results of the Modified Food Security Quotient in West Java showed that from the Food Availability Aspect with 13 measurement variables, then from the Food Access Aspect with 11 measurement variables, and from the Food Quality/Utilization Aspect with 13 measurement variables. The condition of food security in general is very safe (30% of West Java) and safe (70% of West Java), although in several districts and cities, there are still measuring variables that still need improvement, such as the area of land receiving irrigation water , production of sweet potatoes, corn, rice, harvested area of corn, rice, and cassava production, then total working population, road length and road conditions (state, province, district/city), number of health workers, number of hospitals and number of clinics.